1941
DOI: 10.1152/ajplegacy.1941.134.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Excretion of Urogastrone

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1942
1942
1971
1971

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There is no good evidence that urogastrone is related to enterogastrone; the results of experiments to determine the effect of enterectomy on urogastrone excretion in dogs are inconclusive (Culmer, Gray, Adkison & Ivy, 1940;Gray, Culmer, Wells & Wieczorowski, 1941). However, these and numerous other attempts to study the excretion of urogastrone activity in various circumstances (Friedman, 1951) are of doubtful value since it has never been shown that any method so far employed for the extraction of urogastrone activity from urine is trustworthy.…”
mentioning
confidence: 99%
“…There is no good evidence that urogastrone is related to enterogastrone; the results of experiments to determine the effect of enterectomy on urogastrone excretion in dogs are inconclusive (Culmer, Gray, Adkison & Ivy, 1940;Gray, Culmer, Wells & Wieczorowski, 1941). However, these and numerous other attempts to study the excretion of urogastrone activity in various circumstances (Friedman, 1951) are of doubtful value since it has never been shown that any method so far employed for the extraction of urogastrone activity from urine is trustworthy.…”
mentioning
confidence: 99%
“…Posterior pituitary hormones are known to inhibit gastric secretion (Dodds, Hills, Noble, and Williams, 1935;Gray, Culmer, Wells, and Wieczorowski, 1941;Wolf and Wolff, 1947) probably by their vasoconstrictor action (Cutting, Dodds, Noble, and Williams, 1937), and we have found vasopressin to be an effective inhibitor of histamine secretion in rats. The inhibitory effect of vasopressin is readily reversible so that in an assay there is relatively little interference from one dose to the next.…”
mentioning
confidence: 55%
“…It is well known that human and animal urines contain a substance called urogastrone (Gray, Culmer, Wells & Wieczorowski, 1941), which inhibits gastric secretion (Friedman, 1951). The properties of the substance and its extraction from urine have been studied extensively by Gray, Wieczorowski, Wells & Harris (1942) and Gregory (1955).…”
Section: Effect On Blood Pressurementioning
confidence: 99%